Copolymer, molded article, injection molded article, and coated electric wire

By using copolymers containing TFE and PPVE units, the composition and structure of existing sealing materials are adjusted, and the problem of insufficient sealing properties at high temperatures is solved, and excellent performance at high temperatures is achieved.

CN116867814BActive Publication Date: 2025-04-18DAIKIN INDUSTRIES LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202280016008.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-09-30
Filing Date
2022-01-31
Publication Date
2025-04-18
Estimated Expiration
2042-01-31

AI Technical Summary

Technical Problem

The existing sealing materials have insufficient sealing properties at high temperatures, poor wear resistance and crack resistance, and insufficient oxygen permeability and low reagent permeability.

Method used

The copolymer containing tetrafluoroethylene (TFE) units and perfluoro(propyl vinyl ether) (PPVE) units is used to adjust the content of PPVE units, the melt flow rate and the number of functional groups to improve moldability and high temperature performance.

Benefits of technology

It has achieved excellent sealing properties, wear resistance, low oxygen permeability, low reagent permeability, creep resistance and rigidity and crack resistance at high temperatures of 110°C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004403955380000051
    Figure BDA0004403955380000051
  • Figure BDA0004403955380000181
    Figure BDA0004403955380000181
  • Figure BDA0004403955380000201
    Figure BDA0004403955380000201
Patent Text Reader

Abstract

The present invention provides a copolymer comprising tetrafluoroethylene units and perfluoro(propyl vinyl ether) units, wherein the content of the perfluoro(propyl vinyl ether) units is 3.5% to 4.2% by mass relative to all monomer units, the melt flow rate at 372°C is 34.0 g / 10 min to 42.0 g / 10 min, and the number of functional groups is 10 6 The number of carbon atoms in the main chain is 50 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a copolymer, a molded article, an injection-molded article and a covered electric wire. Background Art

[0002] Patent document 1 describes a sealing material, which is a sealing material composed of a fluorine-containing polymer having a polymerization unit based on tetrafluoroethylene and a polymerization unit based on one or more perfluoro(alkyl vinyl ether), characterized in that the polymerization unit based on perfluoro(alkyl vinyl ether) of the above-mentioned fluorine-containing polymer is 4.0% by mass or less relative to all the polymerization units, and the melt flow rate is 0.1 g / 10 min to 100 g / 10 min.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2013-177574 Summary of the invention

[0006] Problems to be solved by the invention

[0007] The object of the present invention is to provide a copolymer which can obtain an injection-molded body having excellent surface smoothness with high productivity by injection molding, can form a coating layer with few defects by extrusion molding, and can obtain a molded body having excellent sealing properties at high temperatures, wear resistance, low oxygen permeability, low reagent permeability, creep resistance, rigidity at a high temperature of 110°C, and crack resistance.

[0008] Means for solving problems

[0009] According to the present invention, a copolymer is provided, which contains tetrafluoroethylene units and perfluoro(propyl vinyl ether) units, wherein the content of the perfluoro(propyl vinyl ether) units is 3.5% to 4.2% by mass relative to all monomer units, the melt flow rate at 372°C is 34.0 g / 10 minutes to 42.0 g / 10 minutes, and the number of functional groups is 10 6 The number of carbon atoms in the main chain is 50 or less.

[0010] Furthermore, according to the present invention, there is provided an injection-molded article comprising the above-mentioned copolymer.

[0011] Furthermore, according to the present invention, there is provided a covered electric wire comprising a covering layer containing the above-mentioned copolymer.

[0012] Furthermore, according to the present invention, there is provided a molded article comprising the above-mentioned copolymer, wherein the above-mentioned molded article is a gasket or a wire covering.

[0013] Effects of the Invention

[0014] According to the present invention, a copolymer can be provided, which can obtain an injection-molded body having excellent surface smoothness with high productivity by injection molding, can form a coating layer with few defects by extrusion molding, and can obtain a molded body having excellent sealing properties at high temperatures, wear resistance, low oxygen permeability, low reagent permeability, creep resistance, and rigidity and crack resistance at a high temperature of 110°C. DETAILED DESCRIPTION

[0015] Hereinafter, specific embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments.

[0016] The copolymer of the present invention contains tetrafluoroethylene (TFE) units and perfluoro(propyl vinyl ether) (PPVE) units.

[0017] Patent document 1 states that in-vehicle secondary batteries are sometimes exposed to high temperatures above 85°C in the operating environment. In order to maintain the airtightness and liquid-tightness inside the battery, it is important that the sealing material can maintain sufficient compression recovery even under such harsh operating conditions and maintain high sealing between the battery can and the sealing body.

[0018] However, the existing sealing material described in Patent Document 1 has problems such as low oxygen permeability, insufficient rigidity at a high temperature of 110°C, and low permeability to reagents such as electrolytes. Gaskets used in sliding parts, opening and closing parts, etc., require not only sealing properties at high temperatures, wear resistance, creep resistance, and crack resistance, but also low oxygen permeability, rigidity at a high temperature of 110°C, and low permeability to reagents such as electrolytes. Furthermore, gaskets are usually manufactured by injection molding, so they are also required to be easily molded by injection molding and have a smooth surface of the obtained injection molded body.

[0019] It was found that by appropriately adjusting the content of PPVE units, melt flow rate (MFR) and number of functional groups of a copolymer containing TFE units and PPVE units, the moldability of the copolymer can be significantly improved, and a molded product having excellent sealing properties at high temperatures, wear resistance, creep resistance and crack resistance can be obtained, and a molded product having low oxygen permeability, high rigidity at a high temperature of 110°C and low permeability to reagents such as electrolytes can be obtained. Therefore, by using the copolymer of the present invention, a molded product such as a gasket that exhibits excellent sealing properties even at high temperatures, suppresses the occurrence of wear, deformation or cracks during repeated sliding and opening and closing, and is less likely to allow oxygen and reagents to permeate can be realized.

[0020] Furthermore, by extruding the copolymer of the present invention onto a core wire by extrusion molding, a coating layer with few defects can be formed. Thus, the copolymer of the present invention can be used not only as a material for sealing members such as gaskets, but also for a wide range of applications such as wire coating.

[0021] The copolymer of the present invention is a melt-processable fluororesin. Melt-processability means that the polymer can be melted and processed using existing processing equipment such as an extruder and an injection molding machine.

[0022] The content of the PPVE unit of the copolymer is 3.5% to 4.2% by mass relative to the total monomer units. The content of the PPVE unit of the copolymer is preferably 3.6% by mass or more, preferably 4.1% by mass or less, and more preferably 4.0% by mass or less. If the content of the PPVE unit of the copolymer is too much, the sealing property at high temperature, low oxygen permeability, low reagent permeability, creep resistance and rigidity at high temperature of 110°C of the molded body obtained from the copolymer are poor. If the content of the PPVE unit of the copolymer is too little, the wear resistance and crack resistance of the molded body obtained from the copolymer are poor.

[0023] The content of the TFE unit of the copolymer is preferably 95.8% to 96.5% by mass relative to the total monomer units, more preferably 95.9% by mass or more, further preferably 96.0% by mass or more, and more preferably 96.4% by mass or less. If the content of the TFE unit of the copolymer is too small, the sealing property at high temperature, low oxygen permeability, low reagent permeability, creep resistance and rigidity at high temperature of 110°C of the molded body obtained from the copolymer may be deteriorated. If the content of the TFE unit of the copolymer is too much, the wear resistance and crack resistance of the molded body obtained from the copolymer may be deteriorated.

[0024] In the present invention, the content of each monomer unit in the copolymer is determined by 19 Determined by F-NMR method.

[0025] The copolymer may also contain monomer units derived from monomers copolymerizable with TFE and PPVE. In this case, the content of the monomer units copolymerizable with TFE and PPVE is preferably 0 to 1.5% by mass, more preferably 0.05% to 0.7% by mass, and further preferably 0.1% to 0.5% by mass relative to all monomer units of the copolymer.

[0026] Examples of monomers copolymerizable with TFE and PPVE include hexafluoropropylene (HFP), CZ 1 Z 2 =CZ 3 (CF2) n Z 4 (Where Z 1 , Z 2 and Z 3 Same or different, means H or F, Z 4 represents H, F or Cl, n represents an integer from 2 to 10) a vinyl monomer, CF2=CF-ORf 1 (Where Rf1 Perfluoro(alkyl vinyl ether) [PAVE] (except PPVE) represented by a perfluoroalkyl group having 1 to 8 carbon atoms), and CF2=CF-OCH2-Rf 1 (Rf 1 represents a perfluoroalkyl group having 1 to 5 carbon atoms. ) and the like. Among them, HFP is preferred.

[0027] The copolymer is preferably at least one selected from the group consisting of a copolymer consisting only of a TFE unit and a PPVE unit and a TFE / HFP / PPVE copolymer, and more preferably a copolymer consisting only of a TFE unit and a PPVE unit.

[0028] The melt flow rate (MFR) of the copolymer is 34.0 g / 10 minutes to 42.0 g / 10 minutes. The MFR of the copolymer is preferably 34.1 g / 10 minutes or more, more preferably 35.0 g / 10 minutes or more, further preferably 35.1 g / 10 minutes or more, particularly preferably 35.5 g / 10 minutes or more, preferably 41.0 g / 10 minutes or less, more preferably 40.0 g / 10 minutes or less, and further preferably 39.0 g / 10 minutes or less. If the MFR of the copolymer is too low, it is difficult to obtain an injection molded body with excellent surface smoothness when the copolymer is injected by injection molding, or the molded body obtained from the copolymer has poor oxygen permeability, reagent permeability, and rigidity at a high temperature of 110°C. If the MFR of the copolymer is too high, the molded body obtained from the copolymer has poor sealing performance, wear resistance, and crack resistance at high temperatures.

[0029] In the present invention, MFR is a value obtained as the mass (g / 10 minutes) of a polymer flowing out from a nozzle having an inner diameter of 2.1 mm and a length of 8 mm at 372° C. and a load of 5 kg per 10 minutes using a melt indexer in accordance with ASTM D1238.

[0030] The MFR can be adjusted by adjusting the type and amount of the polymerization initiator, the type and amount of the chain transfer agent, etc., used when polymerizing the monomers.

[0031] In the present invention, every 10 6 The number of functional groups per main chain carbon atom is 50 or less. 6 The number of functional groups per main chain carbon atom is preferably 40 or less, more preferably 30 or less, still more preferably 20 or less, further preferably 15 or less, particularly preferably 10 or less, and most preferably less than 6. By setting the number of functional groups of the copolymer within the above range, a molded product having excellent sealing properties at high temperatures, low oxygen permeability, low reagent permeability, and creep resistance can be obtained.

[0032] The identification of the types of the functional groups and the measurement of the number of the functional groups can be performed using infrared spectroscopy.

[0033] The number of functional groups is specifically determined by the following method. First, the copolymer is formed by cold pressing to produce a film with a thickness of 0.25 mm to 0.3 mm. The film is analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum of the copolymer, and a differential spectrum with a background spectrum of fully fluorinated functional groups without any functional groups is obtained. The number of functional groups in the copolymer relative to each 1×10 6 The number of functional groups N per carbon atom.

[0034] N=I×K / t(A)

[0035] I: Absorbance

[0036] K: Correction coefficient

[0037] t: film thickness (mm)

[0038] For reference, absorption frequencies, molar absorption coefficients, and correction coefficients for some functional groups are shown in Table 1. The molar absorption coefficients were determined from FT-IR measurement data of low-molecular model compounds.

[0039] [Table 1]

[0040] Table 1

[0041]

[0042] The absorption frequencies of -CH2CF2H, -CH2COF, -CH2COOH, -CH2COOCH3, and -CH2CONH2 are several tens of kaise (cm-1) lower than those of -CF2H, -COF, free -COOH, and bound -COOH, -COOCH3, and -CONH2, respectively, as shown in the table. 1 ).

[0043] For example, the functional group number of -COF is the absorption frequency 1883 cm-1 due to -CF2COF. 1 The number of functional groups obtained from the absorption peak at 1840 cm-1 due to -CH2COF 1 The total number of functional groups found from the absorption peak at .

[0044] The functional groups are functional groups present at the main chain end or side chain end of the copolymer and functional groups present in the main chain or side chain. The number of functional groups can be the total number of -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2 and -CH2OH.

[0045] The functional groups are introduced into the copolymers, for example, by chain transfer agents or polymerization initiators used when manufacturing the copolymers. For example, when alcohol is used as a chain transfer agent or a peroxide having a -CH2OH structure is used as a polymerization initiator, -CH2OH is introduced into the main chain end of the copolymer. In addition, by polymerizing monomers having functional groups, the functional groups are introduced into the side chain ends of the copolymers.

[0046] By fluorinating the copolymer having such functional groups, a copolymer having the number of functional groups within the above range can be obtained. That is, the copolymer of the present invention is preferably a fluorinated copolymer. The copolymer of the present invention also preferably has a -CF3 terminal group.

[0047] The melting point of the copolymer is preferably 295° C. to 315° C., more preferably 300° C. or higher, further preferably 303° C. or higher, particularly preferably 304° C. or higher, and more preferably 310° C. or lower. By setting the melting point within the above range, a copolymer can be obtained that can provide a molded body having better moldability, better sealing performance at high temperatures, better wear resistance, lower oxygen permeability, lower reagent permeability, better creep resistance, and better rigidity and crack resistance at a high temperature of 110° C.

[0048] In the present invention, the melting point can be measured using a differential scanning calorimeter [DSC].

[0049] The storage modulus (E') of the copolymer at 150°C is preferably 115 MPa or more, more preferably 120 MPa or more, further preferably 125 MPa or more, and preferably 1000 MPa or less, more preferably 500 MPa or less, further preferably 300 MPa or less. By setting the storage modulus (E') of the copolymer at 150°C within the above range, a copolymer that provides a molded body with excellent sealing properties at high temperatures can be obtained.

[0050] The storage modulus (E') can be measured by dynamic viscoelasticity measurement at a temperature increase rate of 2°C / min and a frequency of 10 Hz in the range of 30°C to 250°C. The storage modulus (E') at 150°C can be increased by adjusting the content of the PPVE unit and the melt flow rate (MFR) of the copolymer.

[0051] The repulsion force of the copolymer at 150°C is preferably 0.55 MPa or more, more preferably 0.60 MPa or more, and the upper limit is not particularly limited, and may be 1.00 MPa or less. The repulsion force at 150°C can be increased by adjusting the content of the PPVE unit, the melt flow rate (MFR) and the number of functional groups of the copolymer. High repulsion means that the molded body formed by the copolymer has excellent sealing properties at high temperatures.

[0052] The repulsive force can be calculated as follows: a test piece obtained from a copolymer is deformed at a compression deformation rate of 50%, and then placed at 150°C for 18 hours. The compression is released, and the test piece is placed at room temperature for 30 minutes. The height of the test piece (the height of the test piece after compression deformation) is measured, and the repulsive force can be calculated from the height of the test piece after compression deformation and the storage modulus (MPa) at 150°C using the following formula.

[0053] 150℃ repulsion (MPa) = (t2-t1) / t1×E'

[0054] t1: Original height of the test piece before compression deformation (mm) × 50%

[0055] t2: Height of the test piece after compression deformation (mm)

[0056] E': Storage modulus at 150°C (MPa)

[0057] The oxygen permeability coefficient of the copolymer is preferably 630 cm 3 mm / (m 2 ·24h·atm) or less. The copolymer of the present invention has excellent low oxygen permeability because the content of the PPVE unit, the melt flow rate (MFR) and the number of functional groups of the copolymer containing TFE units and PPVE units are appropriately adjusted. Therefore, oxygen is not easy to permeate the molded body formed by the copolymer, so, for example, the sealing member formed by the copolymer of the present invention can be suitably used for sealing the piping for transporting reagents that should be avoided from oxidation.

[0058] In the present invention, the oxygen permeability coefficient can be measured under the conditions of a test temperature of 70° C. and a test humidity of 0% RH. The specific measurement of the oxygen permeability coefficient can be carried out by the method described in the Examples.

[0059] The electrolyte permeability of the copolymer is preferably 6.0 g·cm / m 2 The copolymer of the present invention has excellent low permeability to electrolytes because the content of PPVE units, melt flow rate (MFR) and number of functional groups of the copolymer containing TFE units and PPVE units are appropriately adjusted. That is, by using the copolymer of the present invention, a molded body that is not easy to allow reagents such as electrolytes to pass through can be obtained.

[0060] In the present invention, the electrolyte permeability can be measured under the conditions of a temperature of 60° C. and 30 days. The electrolyte permeability can be specifically measured by the method described in the Examples.

[0061] The copolymer of the present invention can be manufactured by polymerization methods such as suspension polymerization, solution polymerization, emulsion polymerization, bulk polymerization, etc. As the polymerization method, emulsion polymerization or suspension polymerization is preferred. In these polymerizations, various conditions such as temperature and pressure, polymerization initiator, and other additives can be appropriately set according to the composition and amount of the copolymer.

[0062] As the polymerization initiator, an oil-soluble radical polymerization initiator or a water-soluble radical polymerization initiator can be used.

[0063] The oil-soluble radical polymerization initiator may be a known oil-soluble peroxide, and the following may be cited as representative examples:

[0064] Dialkyl peroxydicarbonates such as di-n-propyl peroxydicarbonate, di-isopropyl peroxydicarbonate, di-sec-butyl peroxydicarbonate and di-2-ethoxyethyl peroxydicarbonate;

[0065] Peroxyesters such as tert-butyl peroxyisobutyrate and tert-butyl peroxypivalate;

[0066] Dialkyl peroxides such as di-tert-butyl peroxide;

[0067] Di[fluoro(or chlorofluoro)acyl]peroxides; etc.

[0068] Examples of the di[fluoro(or fluorochloro)acyl]peroxides include diacyl peroxides represented by [(RfCOO)-]2 (Rf is a perfluoroalkyl group, an ω-hydroperfluoroalkyl group or a fluorochloroalkyl group).

[0069] Examples of the di[fluoro(or chlorofluoro)acyl]peroxides include di(ω-hydro-dodecafluorohexanoyl)peroxide, di(ω-hydro-tetrafluoroheptanoyl)peroxide, di(ω-hydro-hexafluorononanoyl)peroxide, di(perfluoropropionyl)peroxide, di(perfluorobutyryl)peroxide, di(perfluorovaleranoyl)peroxide, di(perfluorohexanoyl)peroxide, di(perfluoroheptanoyl)peroxide, di(perfluorooctanoyl)peroxide, di(perfluorononanoyl)peroxide, di(ω-chloro-hexafluorobutyryl ... (ω-chloro-decafluorohexanoyl) peroxide, bis(ω-chloro-tetrafluorooctanoyl) peroxide, ω-hydro-dodecafluoroheptanoyl-ω-hydrohexafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydro-dodecafluoroheptanoyl-peroxide, ω-hydro-dodecafluoroheptanoyl-perfluorobutyryl-peroxide, bis(dichloropentafluorobutyryl) peroxide, bis(trichlorooctafluorohexanoyl) peroxide, bis(tetrachloroundecanoyl) peroxide, bis(pentachlorotetrafluorodecanoyl) peroxide, bis(undecachlorotriacontafluorodocosanoyl) peroxide, and the like.

[0070] The water-soluble free radical polymerization initiator may be a known water-soluble peroxide, for example, ammonium salts, potassium salts, sodium salts of persulfuric acid, perboric acid, perchloric acid, perphosphoric acid, percarbonic acid, etc., organic peroxides such as disuccinic acid peroxide and diglutaric acid peroxide, tert-butyl peroxymaleate, tert-butyl hydroperoxide, etc. A reducing agent such as sulfites may be used in combination with the peroxide, and the amount used may be 0.1 to 20 times that of the peroxide.

[0071] In the polymerization, a surfactant, a chain transfer agent, and a solvent may be used, and conventionally known surfactants, chain transfer agents, and solvents may be used.

[0072] As the surfactant, known surfactants can be used, for example, nonionic surfactants, anionic surfactants, cationic surfactants, etc. can be used. Among them, fluorinated anionic surfactants are preferred, and more preferred are fluorinated anionic surfactants that may or may not contain ether-bonded oxygen (i.e., oxygen atoms can be inserted between carbon atoms) and have a linear or branched carbon number of 4 to 20. The amount of surfactant added (relative to polymerization water) is preferably 50 ppm to 5000 ppm.

[0073] Examples of chain transfer agents include hydrocarbons such as ethane, isopentane, n-hexane, and cyclohexane; aromatics such as toluene and xylene; ketones such as acetone; acetates such as ethyl acetate and butyl acetate; alcohols such as methanol and ethanol; mercaptans such as methyl mercaptan; halogenated hydrocarbons such as carbon tetrachloride, chloroform, dichloromethane, and chloromethane; etc. The amount of the chain transfer agent added may vary depending on the chain transfer constant of the compound used, and is usually used in the range of 0.01% to 20% by mass relative to the polymerization solvent.

[0074] Examples of the solvent include water and a mixed solvent of water and alcohol.

[0075] In suspension polymerization, in addition to water, fluorinated solvents can also be used. Examples of fluorinated solvents include hydrochlorofluoroalkanes such as CH3CClF2, CH3CCl2F, CF3CF2CCl2H, CF2ClCF2CFHCl, etc.; chlorofluoroalkanes such as CF2ClCFClCF2CF3, CF3CFClCFClCF3, etc.; hydrofluoroalkanes such as CF3CFHCFHCF2CF2CF3, CF2HCF2CF2CF2CF2H, CF3CF2CF2CF2CF2CF2CF2H, etc.; CH3OC2F5, C Hydrofluoroethers such as H3OC3F5CF3CF2CH2OCHF2, CF3CHFCF2OCH3, CHF2CF2OCH2F, (CF3)2CHCF2OCH3, CF3CF2CH2OCH2CHF2, CF3CHFCF2OCH2CF3, etc.; perfluorocyclobutane, CF3CF2CF2CF3, CF3CF2CF2CF2CF3, CF3CF2CF2CF2CF2CF3, etc., perfluoroalkanes, among which perfluoroalkanes are preferred. From the perspective of suspension and economy, the amount of fluorine-based solvent used is preferably 10% to 100% by mass relative to the aqueous medium.

[0076] The polymerization temperature is not particularly limited and may be 0 to 100° C. The polymerization pressure is appropriately determined depending on the type and amount of the solvent used and other polymerization conditions such as vapor pressure and polymerization temperature, and may generally be 0 to 9.8 MPaG.

[0077] In the case of obtaining an aqueous dispersion containing a copolymer by polyreaction, the copolymer contained in the aqueous dispersion can be precipitated, and the copolymer can be washed and dried to recover the copolymer. In addition, in the case of obtaining a copolymer in the form of slurry by polyreaction, the slurry can be taken out from a reaction vessel, and the copolymer can be washed and dried to recover the copolymer. The copolymer can be recovered in the form of a powder by drying.

[0078] The copolymer obtained by polymerization can also be formed into pellets. There is no particular limitation on the molding method for forming the pellets, and a conventionally known method can be used. For example, a method of using a single-screw extruder, a twin-screw extruder, or a tandem extruder to melt-extrude the copolymer, cut it into a predetermined length, and mold it into pellets, etc. can be cited. The extrusion temperature during melt extrusion needs to be changed according to the melt viscosity and the manufacturing method of the copolymer, and is preferably the melting point of the copolymer + 20°C to the melting point of the copolymer + 140°C. There is no particular limitation on the cutting method of the copolymer, and conventionally known methods such as a wire cutting method, a heat cutting method, an underwater cutting method, and a sheet cutting method can be used. The volatile components in the pellets can also be removed by heating the obtained pellets (degassing treatment). The obtained pellets can also be treated by contacting with warm water at 30°C to 200°C, steam at 100°C to 200°C, or hot air at 40°C to 200°C.

[0079] The copolymer obtained by polymerization can also be subjected to fluorination treatment. Fluorination treatment can be carried out by contacting the copolymer that has not been fluorinated with a fluorine-containing compound. Through fluorination treatment, thermally unstable functional groups such as -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2 and relatively thermally stable functional groups such as -CF2H of the copolymer can be converted into extremely thermally stable -CF3. As a result, the total number (number of functional groups) of -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2 and -CF2H of the copolymer can be easily adjusted to the above range.

[0080] The fluorine-containing compound is not particularly limited, and a fluorine radical source that generates fluorine radicals under fluorination conditions can be cited. As the above-mentioned fluorine radical source, F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, fluorinated halogens (such as IF5, ClF3), etc. can be cited.

[0081] The fluorine free radical source such as F2 gas can be 100% concentration, but from the aspect of safety, it is preferably mixed with an inert gas and diluted to 5% to 50% by mass for use, and more preferably diluted to 15% to 30% by mass for use. As the above-mentioned inert gas, nitrogen, helium, argon, etc. can be cited, and nitrogen is preferred from the aspect of economy.

[0082] The conditions of the fluorination treatment are not particularly limited, and the copolymer in a molten state may be brought into contact with the fluorine-containing compound, but it may be generally carried out at a temperature below the melting point of the copolymer, preferably at 20°C to 240°C, and more preferably at 100°C to 220°C. The above-mentioned fluorination treatment is generally carried out for 1 hour to 30 hours, preferably for 5 hours to 25 hours. The fluorination treatment is preferably a treatment in which the copolymer that has not been fluorinated is brought into contact with fluorine gas (F2 gas).

[0083] The copolymer of the present invention may be mixed with other components as required to obtain a composition. Other components include fillers, plasticizers, processing aids, mold release agents, pigments, flame retardants, lubricants, light stabilizers, weather stabilizers, conductive agents, antistatic agents, ultraviolet absorbers, antioxidants, foaming agents, fragrances, oils, softeners, dehydrofluorination agents, etc.

[0084] As fillers, for example, silicon dioxide, kaolin, clay, organic clay, talc, mica, aluminum oxide, calcium carbonate, calcium terephthalate, titanium oxide, calcium phosphate, calcium fluoride, lithium fluoride, cross-linked polystyrene, potassium titanate, carbon, boron nitride, carbon nanotubes, glass fibers, etc. can be cited. As conductive agents, carbon black, etc. can be cited. As plasticizers, dioctyl phthalate, pentaerythritol, etc. can be cited. As processing aids, carnauba wax, sulfone compounds, low molecular weight polyethylene, fluorine-based additives, etc. can be cited. As dehydrofluorination agents, organic onium, amidines, etc. can be cited.

[0085] As the other components, other polymers other than the above copolymers may be used. Examples of the other polymers include fluororesins, fluororubbers, and non-fluorinated polymers other than the above copolymers.

[0086] Examples of the method for producing the composition include a method of dry-mixing the copolymer and other components; a method of preliminarily mixing the copolymer and other components with a mixer and then melt-kneading them with a kneader, melt extruder or the like; and the like.

[0087] The copolymer of the present invention or the above-mentioned composition can be used as a processing aid, a molding material, etc., and is preferably used as a molding material. The aqueous dispersion, solution, suspension, and copolymer / solvent system of the copolymer of the present invention can also be utilized, and they can be applied as a coating, or used for encapsulation, impregnation, or film casting. However, the copolymer of the present invention has the above-mentioned characteristics, and is therefore preferably used as the above-mentioned molding material.

[0088] The copolymer of the present invention or the above-mentioned composition may be molded to obtain a molded product.

[0089] The method for molding the above-mentioned copolymer or the above-mentioned composition is not particularly limited, and injection molding, extrusion molding, compression molding, blow molding, transfer molding, rotational molding, roto-lining molding, etc. can be cited. As a molding method, among them, extrusion molding, compression molding, injection molding or transfer molding are preferred, and injection molding, extrusion molding or transfer molding are more preferred because molded bodies can be produced with high productivity, and injection molding is further preferred. That is, as a molded body, extrusion molding, compression molding, injection molding or transfer molding are preferably used, and injection molding, extrusion molding or transfer molding are more preferably used because they can be produced with high productivity, and injection molding, extrusion molding or transfer molding are more preferably used, and injection molding is further preferred. By molding the copolymer of the present invention by injection molding, an injection molded body with excellent surface smoothness can be obtained with high productivity.

[0090] Examples of the molded article containing the copolymer of the present invention include nuts, bolts, joints, films, bottles, washers, wire coatings, tubes, hoses, pipes, valves, sheets, seals, gaskets, tanks, rollers, containers, cocks, connectors, filter housings, filter covers, flow meters, pumps, wafer carriers, wafer boxes, and the like.

[0091] The copolymer of the present invention, the composition or the molded article can be used, for example, in the following applications.

[0092] Films for food packaging, lining materials for fluid delivery pipelines used in food manufacturing processes, gaskets, sealing materials, sheets and other fluid delivery components for food manufacturing equipment;

[0093] Chemical plugs, packaging films, lining materials for fluid delivery pipelines used in chemical manufacturing processes, gaskets, sealing materials, thin plates and other reagent delivery components;

[0094] Lining components for the inner surface of reagent tanks and piping in chemical equipment and semiconductor factories;

[0095] O (square) rings / tubes / gaskets, valve core materials, hoses, sealing materials, etc. used in automobile fuel systems and peripheral devices; fuel delivery components such as hoses and sealing materials used in automobile AT devices;

[0096] Flange gaskets, shaft seals, valve stem seals, sealing materials, hoses, etc. used in car engines and peripheral devices of automobiles; other automobile components such as automobile brake hoses, air conditioning hoses, radiator hoses, wire covering materials, etc.;

[0097] O (square) rings, tubes, gaskets, valve core materials, hoses, sealing materials, rollers, gaskets, diaphragms, joints and other reagent delivery components for semiconductor manufacturing equipment;

[0098] Coating rollers, hoses, tubes, ink containers and other coating and ink components for coating equipment;

[0099] Food and beverage conveying components such as tubes or hoses for food and beverages, tubes, hoses, belts, gaskets, joints, etc., food packaging materials, and glass cooking equipment;

[0100] Waste liquid transmission components such as pipes and hoses used for waste liquid transmission;

[0101] Components for high-temperature liquid transmission such as pipes and hoses used for high-temperature liquid transmission;

[0102] Steam piping components such as pipes and hoses used for steam piping;

[0103] Pipe corrosion protection tapes such as tapes wrapped around pipes on ship decks, etc.

[0104] Various covering materials such as wire covering materials, optical fiber covering materials, transparent surface covering materials and back-side agents provided on the light incident side surface of photovoltaic elements of solar cells;

[0105] Diaphragms of diaphragm pumps and sliding components such as various sealing gaskets;

[0106] Weather-resistant covers for agricultural films, various roofing materials, sidewalls, etc.;

[0107] Interior materials used in the construction field, non-combustible fireproof safety glass and other glass covering materials;

[0108] Lining materials for laminated steel sheets used in the home appliance field, etc.

[0109] Further examples of the fuel delivery member used in the fuel system of the above-mentioned automobile include fuel hoses, filler hoses, evaporator hoses, etc. The above-mentioned fuel delivery member can also be used as a fuel delivery member for sour gasoline, alcohol fuel, and fuel added with gasoline additives such as methyl tert-butyl ether resistance and amine resistance.

[0110] The chemical plug and packaging film have excellent chemical resistance to acids, etc. In addition, as the reagent conveying member, there can also be mentioned a corrosion-resistant tape wound around the piping of chemical equipment.

[0111] Examples of the molded article include automobile radiator water chambers, reagent tanks, bellows, partitions, rollers, gasoline tanks, waste liquid transport containers, high temperature liquid transport containers, fisheries and fish farming tanks, and the like.

[0112] Examples of the molded bodies include automobile bumpers, door trims, instrument panels, food processing equipment, cooking machines, waterproof and oil-proof glass, lighting-related instruments, indicator panels and housings of OA instruments, electrically illuminated signboards, display screens, liquid crystal display screens, mobile phones, printer chassis, electrical and electronic components, groceries, trash cans, bathtubs, integrated bathrooms, ventilation fans, lighting frames, and the like.

[0113] The molded product containing the copolymer of the present invention has excellent sealing properties at high temperatures, wear resistance, low oxygen permeability, low reagent permeability, creep resistance, rigidity at a high temperature of 110°C, and crack resistance, and can therefore be suitably used in nuts, bolts, joints, gaskets, valves, plugs, connectors, filter housings, filter covers, flow meters, pumps, and the like.

[0114] The molded article containing the copolymer of the present invention has excellent sealing properties at high temperatures, wear resistance, low oxygen permeability, low reagent permeability, creep resistance, rigidity at high temperatures of 110°C, and crack resistance, and can therefore be suitably used as compressed members such as gaskets and packings.

[0115] The compressed member of the present invention exhibits a high repulsive force even when deformed at a high compression deformation rate. The compressed member of the present invention can be used in a state of compression deformation at a compression deformation rate of 10% or more, and can be used in a state of compression deformation at a compression deformation rate of 20% or more or 25% or more. By deforming the compressed member of the present invention at such a high compression deformation rate and using it, a certain rebound resilience can be maintained for a long time, and the sealing property and the insulation property can be maintained for a long time.

[0116] The compressed member of the present invention exhibits a high storage modulus, a high recovery amount, and a high repulsive force even when deformed at a high compression deformation rate at a high temperature. The compressed member of the present invention can be used in a state of being compressed and deformed at a compression deformation rate of 10% or more at a temperature of 150°C or more, and can be used in a state of being compressed and deformed at a compression deformation rate of 20% or more or 25% or more at a temperature of 150°C or more. By deforming the compressed member of the present invention at such a high compression deformation rate and using it, a certain rebound resilience can be maintained for a long time even at a high temperature, and the sealing characteristics and insulation characteristics at a high temperature can be maintained for a long time.

[0117] Regarding the above-mentioned compression deformation rate, when the compressed member is used in a compressed state, it is the compression deformation rate of the part with the largest compression deformation rate. For example, when a flat compressed member is used in a compressed state in its thickness direction, it is the compression deformation rate in the thickness direction. In addition, for example, when only a part of the compressed member is used in a compressed state, it is the compression deformation rate of the part with the largest compression deformation rate among the compression deformation rates of the compressed parts.

[0118] The size and shape of the compressed member of the present invention can be appropriately set according to the purpose, and there is no particular limitation. The shape of the compressed member of the present invention can be, for example, annular. In addition, the compressed member of the present invention can have a circular, elliptical, quadrilateral with rounded corners, etc. shape when viewed from above, and has a through hole in its central portion.

[0119] The compressed member of the present invention is preferably used as a member for constituting a non-aqueous electrolyte battery. The compressed member of the present invention is particularly suitable as a member used in a state of contact with the non-aqueous electrolyte in the non-aqueous electrolyte battery due to its excellent low electrolyte permeability. That is, the compressed member of the present invention may have a liquid contact surface with the non-aqueous electrolyte in the non-aqueous electrolyte battery.

[0120] The nonaqueous electrolyte battery is not particularly limited as long as it is a battery having a nonaqueous electrolyte, and examples thereof include lithium ion secondary batteries, lithium ion capacitors, etc. In addition, members constituting the nonaqueous electrolyte battery include sealing members, insulating members, and the like.

[0121] The non-aqueous electrolyte is not particularly limited, and one or more of known solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, etc. can be used. The non-aqueous electrolyte battery can further include an electrolyte. The electrolyte is not particularly limited, and LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, etc. can be used.

[0122] The compressed member of the present invention can be preferably used as a sealing member such as a sealing gasket or a sealing pad, and an insulating member such as an insulating gasket or an insulating sealing pad. A sealing member is a member used to prevent leakage of liquid or gas or intrusion of liquid or gas from the outside. An insulating member is a member used for electrical insulation. The compressed member of the present invention can also be a member used for both sealing and insulation purposes.

[0123] The compressed member of the present invention exhibits a high storage modulus, a high recovery amount, and a high repulsive force even when deformed at a high compression deformation rate at high temperature, and can therefore be suitably used in a high temperature environment. For example, the compressed member of the present invention is preferably used in an environment with a maximum temperature of 40°C or above. For example, the compressed member of the present invention is preferably used in an environment with a maximum temperature of 150°C or above. As examples of situations in which the compressed member of the present invention can reach such a high temperature, for example, after the compressed member is installed in the battery in a compressed state, other battery components are installed in the battery by welding; a situation in which a non-aqueous electrolyte battery generates heat; etc.

[0124] The compressed component of the present invention has excellent low permeability to the electrolyte, and even if it is deformed at a high compression deformation rate at high temperature, it also shows a high storage modulus, a high recovery amount and a high repulsion, so it can be suitable for use as a sealing component for a non-aqueous electrolyte battery or an insulating component for a non-aqueous electrolyte battery. For example, when charging a battery such as a non-aqueous electrolyte secondary battery, the temperature of the battery is sometimes temporarily above 40°C, especially temporarily above 150°C. The compressed component of the present invention is used in a battery such as a non-aqueous electrolyte secondary battery even if it is deformed at a high compression deformation rate at high temperature, and even if it contacts with a non-aqueous electrolyte at high temperature, the high resilience is not impaired. Therefore, when the compressed component of the present invention is used as a sealing component, it has excellent sealing properties, and the sealing properties can be maintained for a long time even at high temperatures. In addition, the compressed component of the present invention has excellent insulating properties because it contains the above-mentioned copolymer. Therefore, when the compressed component of the present invention is used as an insulating component, it is firmly fitted with two or more conductive components to prevent short circuits for a long time.

[0125] By molding the copolymer of the present invention by an extrusion molding method, even when the diameter of the core wire is small, the coating will not be broken, and a coating layer can be thinly formed on the core wire with a small diameter at a high pulling speed, and a coating layer with excellent electrical properties can be formed, so the copolymer of the present invention can be suitably used as a material for forming a wire coating. Therefore, the coated wire having a coating layer containing the copolymer of the present invention has almost no defects such as spark generation even when the diameter of the core wire is small and the coating layer is thin, and has excellent electrical properties.

[0126] The covered electric wire comprises a core wire and a covering layer disposed around the core wire and containing the copolymer of the present invention. For example, an extruded body formed by melt-extruding the copolymer of the present invention on the core wire can be used as the covering layer. The covered electric wire is suitable for LAN cables (Eathernet Cable), high-frequency transmission cables, flat cables, heat-resistant cables, etc., and is suitable for transmission cables such as LAN cables (Eathernet Cable) and high-frequency transmission cables.

[0127] As the material of the core wire, for example, a metal conductor material such as copper or aluminum can be used. The core wire preferably has a diameter of 0.02 mm to 3 mm. The core wire diameter is more preferably 0.04 mm or more, further preferably 0.05 mm or more, and particularly preferably 0.1 mm or more. The core wire diameter is more preferably 2 mm or less.

[0128] As specific examples of the core wire, AWG (American Wire Gauge)-46 (solid copper wire with a diameter of 40 μm), AWG-26 (solid copper wire with a diameter of 404 μm), AWG-24 (solid copper wire with a diameter of 510 μm), AWG-22 (solid copper wire with a diameter of 635 μm), etc. can be used.

[0129] The thickness of the coating layer is preferably 0.1 mm to 3.0 mm, and the thickness of the coating layer is also preferably 2.0 mm or less.

[0130] As a high-frequency transmission cable, a coaxial cable can be cited. A coaxial cable generally has a structure in which an inner conductor, an insulating coating, an outer conductor layer and a protective coating are sequentially stacked from the core to the periphery. A molded body containing the copolymer of the present invention can be suitably used as an insulating coating containing a copolymer. The thickness of each layer in the above structure is not particularly limited. Generally, the diameter of the inner conductor is about 0.1 mm to 3 mm, the thickness of the insulating coating is about 0.3 mm to 3 mm, the thickness of the outer conductor layer is about 0.5 mm to 10 mm, and the thickness of the protective coating is about 0.5 mm to 2 mm.

[0131] The coating layer may contain air bubbles, and the air bubbles are preferably uniformly distributed in the coating layer.

[0132] The average bubble diameter of the bubbles is not limited, and is, for example, preferably 60 μm or less, more preferably 45 μm or less, further preferably 35 μm or less, further preferably 30 μm or less, particularly preferably 25 μm or less, and particularly preferably 23 μm or less. In addition, the average bubble diameter is preferably 0.1 μm or more, more preferably 1 μm or more. The average bubble diameter can be obtained by obtaining an electron microscope image of a cross section of the wire, calculating the diameter of each bubble by image processing, and averaging them.

[0133] The foaming rate of the coating layer may be 20% or more. More preferably, it is 30% or more, further preferably, it is 33% or more, and further preferably, it is 35% or more. The upper limit is not particularly limited, and is, for example, 80%. The upper limit of the foaming rate may also be 60%. The foaming rate is a value calculated as ((specific gravity of the wire coating material - specific gravity of the coating layer) / specific gravity of the wire coating material) × 100. The foaming rate can be appropriately adjusted according to the application by, for example, adjusting the amount of gas inserted in the extruder described later, or by selecting the type of dissolved gas.

[0134] The covered electric wire may also have other layers between the core wire and the covering layer, and may further have other layers (outer layers) around the covering layer. When the covering layer contains bubbles, the electric wire of the present invention may also be a two-layer structure (skin-foam body) in which a non-foam layer is inserted between the core wire and the covering layer; a two-layer structure (foam body-skin body) in which the outer layer is covered with a non-foam layer; and a three-layer structure (skin-foam body-skin body) in which the outer layer of the skin-foam body is covered with a non-foam layer. The non-foam layer is not particularly limited, and may be a resin layer composed of TFE / HFP copolymers, TFE / PAVE copolymers, TFE / ethylene copolymers, vinylidene fluoride polymers, polyolefin resins such as polyethylene [PE], polyvinyl chloride [PVC] and other resins.

[0135] The covered electric wire can be produced, for example, by heating a copolymer using an extruder and extruding the copolymer onto a core wire in a molten state to form a covering layer.

[0136] When forming the coating, it is also possible to heat the copolymer and, under the state where the copolymer is molten, introduce gas into the copolymer to form the above-mentioned coating containing bubbles. As the gas, for example, a mixture of gases such as chlorodifluoromethane, nitrogen, carbon dioxide or the like or the above-mentioned gases can be used. The gas can be introduced into the heated copolymer in the form of pressurized gas, or it can be produced by mixing a chemical foaming agent in the copolymer. The gas dissolves in the copolymer in a molten state.

[0137] Furthermore, the copolymer of the present invention can be suitably used as a material for products for high-frequency signal transmission.

[0138] The high-frequency signal transmission product is not particularly limited as long as it is a product used for the transmission of high-frequency signals, and examples thereof include (1) insulating plates of high-frequency circuits, insulating materials of connecting components, molded plates such as printed wiring boards, (2) molded bodies such as bases and antenna covers of high-frequency vacuum tubes, and (3) coated wires such as coaxial cables and LAN cables. The high-frequency signal transmission product can be suitably used in equipment that utilizes microwaves, particularly 3 GHz to 30 GHz microwaves, such as satellite communication equipment and mobile phone base stations.

[0139] In the above-mentioned products for high-frequency signal transmission, the copolymer of the present invention can be suitably used as an insulator because of its low dielectric loss tangent.

[0140] As the above-mentioned (1) molded plate, a printed wiring board is preferred from the aspect of obtaining good electrical characteristics. The above-mentioned printed wiring board is not particularly limited, and examples thereof include printed wiring boards of electronic circuits such as mobile phones, various computers, and communication equipment. As the above-mentioned (2) molded body, a radome is preferred from the aspect of low dielectric loss.

[0141] The copolymer of the present invention is molded by injection molding to obtain a sheet having excellent surface smoothness with high productivity. In addition, the molded body containing the copolymer of the present invention has excellent sealing properties at high temperatures, wear resistance, low oxygen permeability, low reagent permeability, creep resistance, and rigidity and crack resistance at high temperatures of 110°C. Therefore, the molded body containing the copolymer of the present invention can be suitably used as a film or a sheet.

[0142] The film of the present invention is useful as a release film. The release film can be produced by molding the copolymer of the present invention by melt extrusion molding, calendaring molding, press molding, cast molding, etc. From the perspective of obtaining a uniform film, the release film can be produced by melt extrusion molding.

[0143] The film of the present invention can be applied to the surface of a roller used in OA equipment. In addition, the copolymer of the present invention can be formed into a necessary shape by extrusion molding, compression molding, press molding, etc., and formed into a sheet, film, or tube, and used as a surface material for OA equipment rollers or OA equipment belts, etc. In particular, thin-walled tubes and films can be produced by melt extrusion molding.

[0144] The molded article containing the copolymer of the present invention has excellent sealing properties at high temperatures, wear resistance, low oxygen permeability, low reagent permeability, creep resistance, high temperature rigidity at 110° C., and crack resistance, and can therefore be suitably used as bottles or tubes.

[0145] The copolymer of the present invention can be molded into an injection molded body with high productivity by injection molding. Furthermore, the obtained molded body has excellent surface smoothness, excellent sealing performance at high temperature, wear resistance, low oxygen permeability, low reagent permeability, creep resistance, rigidity and crack resistance at a high temperature of 110°C, and can therefore be suitable for use in valves. Therefore, the valve containing the copolymer of the present invention can be manufactured with high productivity, and is not easily damaged or deformed even if repeatedly opened and closed at a high frequency, and has excellent sealing performance at high temperature, low oxygen permeability and low reagent permeability. In the valve of the present invention, at least the liquid contact portion can be composed of the above-mentioned copolymer. In addition, the valve of the present invention can be a valve having a shell containing the above-mentioned copolymer.

[0146] Although the embodiments have been described above, it should be understood that various modifications may be made to the embodiments and details without departing from the spirit and scope of the claims.

[0147] Example

[0148] Next, embodiments of the present invention will be described with reference to examples, but the present invention is not limited to the examples.

[0149] Each numerical value in the examples was measured by the following method.

[0150] (Content of monomer units)

[0151] The content of each monomer unit is measured by an NMR analyzer (for example, AVANCE300 high temperature probe manufactured by Bruker BioSpin).

[0152] (Melt Flow Rate (MFR))

[0153] The mass (g / 10 min) of the polymer flowing out from a nozzle having an inner diameter of 2.1 mm and a length of 8 mm was determined at 372° C. and a load of 5 kg using a melt indexer G-01 (manufactured by Toyo Seiki Seisaku-sho, Ltd.) in accordance with ASTM D1238.

[0154] (Number of functional groups)

[0155] The pellets of the copolymer were formed by cold pressing to produce a film with a thickness of 0.25 mm to 0.3 mm. The film was scanned 40 times by a Fourier transform infrared spectrometer [FT-IR (Spectrum One, manufactured by PerkinElmer)] to obtain an infrared absorption spectrum, and a differential spectrum with a background spectrum of complete fluorination without functional groups was obtained. The absorption peak of a specific functional group in the sample relative to each 1×10 6 The number of functional groups N per carbon atom.

[0156] N=I×K / t (A)

[0157] I: Absorbance

[0158] K: Correction coefficient

[0159] t: film thickness (mm)

[0160] For reference, regarding the functional groups in the present invention, the absorption frequency, molar absorption coefficient and correction coefficient are shown in Table 2. The molar absorption coefficient was determined from the FT-IR measurement data of a low molecular model compound.

[0161] [Table 2]

[0162] Table 2

[0163]

[0164] (Melting Point)

[0165] Using a differential scanning calorimeter (trade name: X-DSC7000, manufactured by Hitachi High-Tech Science Co., Ltd.), the temperature was increased from 200°C to 350°C for the first time at a heating rate of 10°C / min, then cooled from 350°C to 200°C at a cooling rate of 10°C / min, and the temperature was increased from 200°C to 350°C for the second time at a heating rate of 10°C / min. The melting point was determined from the peak of the melting curve generated in the second heating process.

[0166] Comparative Example 1

[0167] 51.8 L of pure water was added to an autoclave of 174 L volume. After nitrogen substitution was fully performed, 40.9 kg of perfluorocyclobutane, 1.79 kg of perfluoro(propyl vinyl ether) (PPVE), and 6.61 kg of methanol were added. The temperature in the system was maintained at 35 ° C and the stirring speed was maintained at 200 rpm. Then, tetrafluoroethylene (TFE) was pressed into 0.64 MPa, and 0.051 kg of a 50% methanol solution of di-n-propyl peroxydicarbonate was added to start polymerization. Since the pressure in the system decreases as the polymerization proceeds, TFE is continuously supplied to keep the pressure constant, and 0.042 kg of PPVE is added for each 1 kg of TFE supplied. When the additional amount of TFE reaches 40.9 kg, the polymerization is terminated. After the unreacted TFE is released and the atmospheric pressure in the autoclave is restored, the obtained reaction product is washed with water and dried to obtain 41.0 kg of powder.

[0168] The obtained powder was melt-extruded at 360° C. using a screw extruder (trade name: PCM46, manufactured by Ikegai Co., Ltd.) to obtain pellets of a TFE / PPVE copolymer. The PPVE content of the obtained pellets was measured by the above-mentioned method.

[0169] The obtained pellets are placed in a vacuum vibration reactor VVD-30 (manufactured by Ohkawara Manufacturing Co., Ltd.) and heated to 210°C. After evacuation, F2 gas diluted with N2 gas to 20 volume % is introduced to atmospheric pressure. 0.5 hours after the introduction of F2 gas, the system is temporarily evacuated and F2 gas is introduced again. Furthermore, 0.5 hours later, the system is evacuated again and F2 gas is introduced again. Thereafter, the above-mentioned F2 gas introduction and evacuation operations are continued once within 1 hour, and the reaction is carried out at a temperature of 210°C for 10 hours. After the reaction is completed, the reactor is fully replaced with N2 gas to terminate the fluorination reaction. Various physical properties are measured using the fluorinated pellets by the above-mentioned method.

[0170] Comparative Example 2

[0171] Fluorinated pellets were obtained in the same manner as in Comparative Example 1 except that PPVE was changed to 1.73 kg, methanol was changed to 4.70 kg, 50% methanol solution of di-n-propyl peroxydicarbonate was changed to 0.103 kg, and PPVE was changed to 0.041 kg additionally added per 1 kg of TFE supplied to obtain 42.6 kg of dry powder.

[0172] Comparative Example 3

[0173] Fluorinated pellets were obtained in the same manner as in Comparative Example 1 except that PPVE was changed to 1.16 kg, methanol was changed to 5.47 kg, 50% methanol solution of di-n-propyl peroxydicarbonate was changed to 0.103 kg, and PPVE was changed to 0.031 kg additionally added per 1 kg of TFE supplied to obtain 42.2 kg of dry powder.

[0174] Comparative Example 4

[0175] Unfluorinated pellets were obtained in the same manner as in Comparative Example 1 except that the amount of methanol was changed to 4.19 kg and the amount of a 50% methanol solution of di-n-propyl peroxydicarbonate was changed to 0.103 kg to obtain 42.6 kg of a dry powder.

[0176] Comparative Example 5

[0177] Fluorinated pellets were obtained in the same manner as in Comparative Example 1 except that PPVE was changed to 2.24 kg, methanol was changed to 2.64 kg, 50% methanol solution of di-n-propyl peroxydicarbonate was changed to 0.103 kg, and PPVE was changed to 0.049 kg additionally added per 1 kg of TFE to obtain 42.9 kg of dry powder.

[0178] Example 1

[0179] Fluorinated pellets were obtained in the same manner as in Comparative Example 1 except that the amount of methanol was changed to 3.60 kg and the amount of a 50% methanol solution of di-n-propyl peroxydicarbonate was changed to 0.103 kg to obtain 42.6 kg of a dry powder.

[0180] Example 2

[0181] Fluorinated pellets were obtained in the same manner as in Comparative Example 1 except that PPVE was changed to 1.73 kg, methanol was changed to 3.81 kg, 50% methanol solution of di-n-propyl peroxydicarbonate was changed to 0.103 kg, and PPVE was changed to 0.041 kg additionally added per 1 kg of TFE supplied to obtain 42.6 kg of dry powder.

[0182] Example 3

[0183] Fluorinated pellets were obtained in the same manner as in Comparative Example 1 except that PPVE was changed to 1.66 kg, methanol was changed to 4.03 kg, 50% methanol solution of di-n-propyl peroxydicarbonate was changed to 0.103 kg, and PPVE was changed to 0.040 kg additionally added per 1 kg of TFE to obtain 42.5 kg of dry powder.

[0184] Example 4

[0185] Fluorinated pellets were obtained in the same manner as in Comparative Example 1 except that PPVE was changed to 1.60 kg, methanol was changed to 4.03 kg, 50% methanol solution of di-n-propyl peroxydicarbonate was changed to 0.103 kg, and PPVE was changed to 0.038 kg additionally added per 1 kg of TFE to obtain 42.5 kg of dry powder.

[0186] Example 5

[0187] PPVE was changed to 1.55 kg, methanol was changed to 4.10 kg, 50% methanol solution of di-n-propyl peroxydicarbonate was changed to 0.103 kg, PPVE was changed to add 0.037 kg for every 1 kg of TFE supplied, the heating temperature of the vacuum vibration reactor was changed to 180°C, and the reaction was changed to 10 hours at 180°C to obtain 42.4 kg of dry powder. Except for this, fluorinated pellets were obtained in the same manner as Comparative Example 1.

[0188] The pellets obtained in Examples and Comparative Examples were used to measure various physical properties by the above-mentioned methods.

[0189] [Table 3]

[0190] Table 3

[0191]

[0192] The expression “<6” in Table 3 means that the number of functional groups is less than 6.

[0193] Next, the following properties were evaluated using the obtained pellets. The results are shown in Table 4.

[0194] (Storage modulus (E'))

[0195] The dynamic viscoelasticity was measured using DVA-220 (manufactured by IT Instrumentation and Control Co., Ltd.). As a sample test piece, a thermoformed piece with a length of 25 mm, a width of 5 mm, and a thickness of 0.2 mm was used, and the measurement was performed in the range of 30°C to 250°C under the conditions of a heating rate of 2°C / min and a frequency of 10 Hz, and the storage modulus (MPa) at 150°C was read.

[0196] (Recovery amount)

[0197] The measurement of the restored amount is based on the method described in ASTM D395 or JIS K6262:2013.

[0198] About 2g of the above pellets were put into a mold (13mm inner diameter, 38mm height), and then melted at 370℃ for 30 minutes using a hot plate press. Then, the molded body with a height of about 8mm was produced while being pressurized with a pressure of 0.2MPa (resin pressure) and water-cooled. After that, a test piece with an outer diameter of 13mm and a height of 6mm was produced by cutting the obtained molded body. Using a compression device, the produced test piece was compressed to a compression deformation rate of 50% at room temperature (that is, a test piece with a height of 6mm was compressed to a height of 3mm). The compressed test piece was fixed to the compression device and placed in an electric furnace at 150℃ for 18 hours. The compression device was removed from the electric furnace, cooled to room temperature, and then the test piece was removed. After the recovered test piece was placed at room temperature for 30 minutes, the height of the recovered test piece was measured, and the recovery amount was calculated by the following formula.

[0199] Recovery amount (mm) = t2 - t1

[0200] t1: Height of spacer (mm)

[0201] t2: Height of the test piece removed from the compression device (mm)

[0202] In the above test, t1 = 3 mm.

[0203] (Repulsion at 150°C)

[0204] The 150° C. repulsion force was calculated by the following formula from the results of the 150° C. compression set test and the results of the 150° C. storage modulus measurement.

[0205] 150℃ repulsion (MPa) = (t2-t1) / t1×E'

[0206] t1: Height of spacer (mm)

[0207] t2: Height of the test piece removed from the compression device (mm)

[0208] E': Storage modulus at 150°C (MPa)

[0209] The molded body with a large repulsive force at 150°C is not easily deformed even at high temperatures and has excellent sealing properties at high temperatures.

[0210] (Abrasion test)

[0211] Using pellets and a hot press molding machine, a sheet test piece with a thickness of about 0.2 mm was made, and a 10 cm × 10 cm test piece was cut out from it. The test piece was fixed on the test bench of a Taber abrasion tester (No. 101 Special Taber Wear Tester, manufactured by Yasuda Seiki Manufacturing Co., Ltd.), and a wear test was performed using the Taber abrasion tester under the conditions of a load of 500 g, a wear wheel CS-10 (grinded with abrasive paper #240 for 20 turns), and a rotation speed of 60 rpm. The weight of the test piece after 1000 turns was measured, and the weight of the test piece was further measured after the same test piece was tested for 10,000 turns. The amount of wear was calculated using the following formula.

[0212] Wear loss (mg) = M1-M2

[0213] M1: Weight of test piece after 1000 revolutions (mg)

[0214] M2: Test piece weight after 10,000 revolutions (mg)

[0215] (Oxygen permeability coefficient)

[0216] Using the pellets and a hot press molding machine, a sheet test piece with a thickness of about 0.1 mm was prepared. The obtained test piece was used to measure the oxygen permeability according to the method described in JIS K7126-1:2006 using a differential pressure gas permeability meter (L100-5000 gas permeability meter, manufactured by Systech illinois). The permeation area was 50.24 cm 2 , the value of oxygen permeability at a test temperature of 70°C and a test humidity of 0% RH. The oxygen permeability coefficient was calculated by the following formula using the obtained oxygen permeability and the thickness of the test piece.

[0217] Oxygen permeability coefficient (cm 3 mm / (m 2 ·24h·atm))=GTR×d

[0218] GTR: oxygen permeability (cm 3 / (m 2 24h atm)

[0219] d: Test piece thickness (mm)

[0220] (Electrolyte Transmittance)

[0221] Using pellets and a hot press molding machine, a sheet test piece with a thickness of about 0.2 mm was prepared. 2) was added with 10g of dimethyl carbonate (DMC), covered with a sheet test piece, and fastened and sealed with a PTFE gasket. The sheet test piece was brought into contact with DMC, kept at a temperature of 60°C for 30 days, then taken out and left at room temperature for 1 hour before measuring the mass loss. The DMC transmittance (g·cm / m 2 ).

[0222] Electrolyte permeability (g·cm / m 2 ) = mass loss (g) × thickness of sheet test piece (cm) / penetration area (m 2 )

[0223] (Evaluation of creep resistance)

[0224] The creep resistance is determined according to the method described in ASTM D395 or JIS K6262:2013. Using pellets and a hot press molding machine, a molded body with an outer diameter of 13 mm and a height of 8 mm is produced. By cutting the obtained molded body, a test piece with an outer diameter of 13 mm and a height of 6 mm is produced. The produced test piece is compressed to a compression deformation rate of 25% at room temperature using a compression device. The compressed test piece is placed in an electric furnace fixed to the compression device and placed at 80°C for 72 hours. The compression device is removed from the electric furnace, cooled to room temperature, and then the test piece is removed. After the recovered test piece is placed at room temperature for 30 minutes, the height of the recovered test piece is measured, and the recovery ratio is calculated by the following formula.

[0225] Recovery ratio (%) = (t2-t1) / t3×100

[0226] t1: Height of spacer (mm)

[0227] t2: Height of the test piece removed from the compression device (mm)

[0228] t3: Height after compression deformation (mm)

[0229] In the above test, t1 = 4.5 mm, t3 = 1.5 mm.

[0230] (110℃ load deflection)

[0231] Using pellets and a hot press molding machine, a sheet test piece with a thickness of about 4.2 mm was made, from which a test piece of 80×10 mm was cut out and heated at 100°C for 20 hours in an electric furnace. In addition to using the obtained test piece, the test was carried out under the conditions of a test temperature of 30°C to 150°C, a heating rate of 120°C / hour, a bending stress of 1.8MPa, and a flatwise method using a heat deformation tester (manufactured by Yasuda Seiki Manufacturing Co., Ltd.) according to the method described in JIS K-K7191-1. The load deflection rate was calculated by the following formula. The sheet with a small load deflection rate of 110°C has excellent rigidity at a high temperature of 110°C.

[0232] Load deflection (%) = a2 / a1×100

[0233] a1: Thickness of the test piece before the test (mm)

[0234] a2: Deflection at 110°C (mm)

[0235] (Bending crack test)

[0236] Use pellets and a hot press molding machine to make a sheet with a thickness of about 2 mm. Use a 13.5 mm × 38 mm rectangular dumbbell to punch out the obtained sheet to obtain three test pieces. In the center of the long side of each obtained test piece, cut a notch with a 19 mm × 0.45 mm blade according to ASTM D1693. Install the three obtained notched test pieces in a stress crack test fixture according to ASTM D1693, visually observe the notch and its surroundings, and count the number of cracks.

[0237] ○: The number of cracks is 0

[0238] ×: The number of cracks is 1 or more

[0239] (Surface smoothness)

[0240] The copolymer was injection molded using an injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., SE50EV-A) at a barrel temperature of 390°C, a mold temperature of 190°C, and an injection speed of 130 mm / s. As a mold, a mold (15 mm×15 mm×0.6 mmt, 4 cavities) in which HPM38 was plated with Cr was used. The surface of the obtained injection molded body was visually observed, and the surface smoothness was evaluated according to the following criteria.

[0241] Advantages: Smooth surface.

[0242] Good: Roughness was observed only on the surface of a portion located near the gate of the mold at 1 / 4 or less.

[0243] Acceptable: Two or four or more rough spots are observed only on the surface of the portion located near the gate of the mold.

[0244] Poor: Roughness was observed over most of the surface.

[0245] (Wire coating characteristics)

[0246] Using the pellets obtained in the examples and comparative examples and boron nitride (BN) having an average particle size of 13.5 μm, a composition having a BN content of 0.75 wt % based on the total amount of the pellets and BN was prepared in the same manner as described in the examples of International Publication No. 03 / 000972.

[0247] The obtained composition and a foaming extruder were used to produce a foamed covered electric wire. The foaming extruder was composed of an extruder and system manufactured by Saint Manufacturing Co., Ltd., a gas injection nozzle manufactured by Micodia Co., Ltd., and a crosshead manufactured by Unitech Co., Ltd. The screw was provided with a mixing zone to uniformly disperse the introduced nitrogen.

[0248] The capacitance was measured online using CAPAC300 19C (manufactured by Zumbach). The foaming rate was managed by online capacitance.

[0249] The wire coating extrusion molding conditions are as follows.

[0250] a) Core conductor: soft steel wire conductor diameter 0.6mm

[0251] b) Coating thickness: 0.25mm

[0252] c) Diameter of coated wire: 1.1mm

[0253] d) Wire pulling speed: 80m / min)

[0254] e) Extrusion conditions:

[0255] · Single screw extruder with barrel diameter = 35mm, L / D = 32

[0256] Mold (inner diameter) / sheet (outer diameter) = 4.7mm / 2.2mm

[0257] The set temperatures of the extruder were: barrel C-1 (330°C), barrel C-2 (360°C), barrel C-3 (370°C), head H-1 (375°C), head H-2 (365°C), head H-3 (360°C). The core wire preheating was set to 90°C.

[0258] f) Nitrogen pressure: 30MPa

[0259] g) Nitrogen flow rate: 15cc / min

[0260] h) Capacitance: 150±3pF / m

[0261] The spark of the obtained covered electric wire was measured at a voltage of 1500V using Beta LaserMike Sparktester HFS1220 on-line.

[0262] The case where the number of sparks per 4500 m was 1 was considered good, the case where it was 0 was considered optimal, and the case where it was 2 or more was considered unacceptable.

[0263] (Dielectric loss tangent)

[0264] The pellets were melt-molded to produce a cylindrical test piece with a diameter of 2 mm. The produced test piece was placed in a 6 GHz cavity resonator manufactured by Kanto Electronics Application Development Co., Ltd. and measured using a network analyzer manufactured by Agilent Technologies. The measurement results were analyzed using the analysis software "CPMA" manufactured by Kanto Electronics Application Development Co., Ltd. on a personal computer connected to the network analyzer, thereby obtaining the dielectric loss tangent (tan δ) at 20°C and 6 GHz.

[0265]

Claims

1. A copolymer comprising tetrafluoroethylene units and perfluoro(propyl vinyl ether) units, The content of the perfluoro(propyl vinyl ether) unit is 3.5% to 4.2% by mass based on the total monomer units. The content of tetrafluoroethylene units is 95.8% to 96.5% by mass based on the total monomer units. The melt flow rate at 372°C is 34.0 g / 10 min to 42.0 g / 10 min. The number of functional groups of -CF=CF2, -CF2H, -COF, -COOH, -COOCH3, -CONH2 and -CH2OH is relative to every 10 6 The number of carbon atoms in the main chain is 50 or less.

2. An injection molded article comprising the copolymer according to claim 1. 3 . A covered electric wire comprising a covering layer containing the copolymer according to claim 1 .

4. A molded product comprising the copolymer according to claim 1, wherein: The molded body is a gasket or a wire covering.

Citation Information

Patent Citations

  • Sealing material

    JP2013177574A

  • Rotor shaft for an open-end spinning rotor

    WO2003000972A1

  • Covered electric wire and coaxial cable

    CN101364456A

  • Sealing material

    CN103946250A